Culturable fungi in Arctic cryoconite holes: A case study from Hansbreen, Spitsbergen - Ogórek, Rafał; Suchodolski, Jakub; Piecuch, Agata; Cal, Magdalena; Spychała, Klaudyna; Dudek, Bartłomiej (Polish Polar Research, 2024)
Extreme cold environments like glaciers, present substantial obstacles to the survival of organisms. Cryoconite, dark sediment covering glacier, provide unique niche for microorganisms. Therefore, we focused on understanding the diversity of fungi in Arctic ecosystems (Hansbreen, Spitsbergen), which is important in the analysis of the structure and of fungi populations. Due to a combination of two incubation temperatures (7°C or 24°C) and two media during isolation (potato dextrose agar, PDA or yeast extract peptone glucose, YPG), and classical/molecular identification approaches, we identified 20 different fungi (17 species and three unassigned species). Most belonged to filamentous fungi within the Ascomycota (19 isolates), with one identified as Basidiomycota-yeast. Regarding growth conditions, both media yielded greater number of fungal cultures at 24°C compared to 7°C. Additionally, PDA was more effective than YPG in isolating fungal cultures. On the other hand, the optimal temperature for achieving the highest CFU (colony–forming unit)/g of sediment was 7°C. The most frequently isolated species was Cladosporium cladosporioides, and to the best of our knowledge, we are the first to detect, the following species in an Arctic environment: Aspergillus jensenii, A. tennesseensis, Peziza varia, and Trichoderma paraviridescens. Additionally, there was a visible increase in the number of fungal propagules but a decrease in their biodiversity towards the upper parts of the glacier. Considering the Arctic amplification there is a need for further research on diversity and function of fungi in glacial ecosystems.